Chinese Fatherhood, Gender and Family : Father Mission - Liong, Mario (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book is about how Chinese men make sense of and practise fatherhood within the context of changing gender conventions and socio-cultural conditions. Liong analyses data from participant observations at a men's centre, focus groups, and in-depth interviews, to assess the subjective experience and identities of Chinese fathers in Hong Kong, from a gender perspective. His findings show that economic provision, education, and marriage are the three "natural" and "normal" domains of paternity. Not being able to fulfil these requirements is a threat to fathers' masculinity, yet is also an opportunity for fathers to reflect upon these accepted conventions. In order to compensate, these men typically develop a closer and more caring relationship with their children, however these fathers still struggle with feelings of inferiority.- Resumé vydavatel
Keywords: otcovství -- Hongkong (Čína); otcovství -- sociální aspekty -- Hongkong (Čína); sexuální role; fatherhood -- Hong Kong (China); fatherhood -- social aspects -- Hong Kong (China); sex role; elektronické knihy; monografie; electronic books; monographs